Pedal bypass for limb-threatening ischaemia: an 11-year review - Eckstein, Hans-Henning; Schumacher, Hardy; Maeder, Norbert; Post, Stefan; Hupp, Thomas; Allenberg, Jens-Rainer (The British journal of surgery, 1996)
Fifty-six patients with limb-threatening ischaemia had pedal revascularization with either autologous vein (n = 39) or sequential composite graft with a 6-mm polytetrafluoroethylene prosthesis and autologous vein (n = 17); 75 per cent had gangrene and skin necrosis and 25 per cent had ischaemic rest pain alone. Twelve grafts occluded within the first week, and resulted in major amputation in eight patients after unsuccessful revision. Two patients required amputation for persistent ischaemia despite a patent bypass. One patient died from bowel perforation (2 per cent). In 47 (84 per cent) of the 56 patients limb and life were preserved. The primary patency rate after 1, 2 and 4 years was 65, 55 and 55 per cent respectively, the secondary patency rate was 71, 62 and 62 per cent, and cumulative limb salvage rates were 77, 71 and 66 per cent. Life-table survival rates during follow-up (median 25 (range 0-112) months) were 89, 78 and 52 per cent respectively after 1, 2 and 4 years. Thirteen of 21 patients who died during follow-up did not require major amputation. Pedal reconstruction with autologous vein provides limb salvage until death in nearly two-thirds of patients with critical limb ischaemia resulting from crural arterial occlusive disease.